2017
DOI: 10.1002/cjoc.201600669
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Electrocatalytic Water Oxidation by a Rigid Macrocyclic Copper(II) Complex

Abstract: A copper(II) complex with a rigid macrocyclic ligand has been synthesized and utilized as a homogeneous electrocatalyst for water oxidation in sodium phosphate buffer at pH 12.0. By using a glassy carbon electrode in a 3 h electrolysis, a high current density of 1.3–1.4 mA/cm2 and a turn‐over number of 4 can be obtained with 1.0 mmol•L−1 of the copper catalyst at an overpotential of 750 mV. Kinetic studies revealed that the electrocatalysis with this complex is a single‐site catalysis with proton‐coupled elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…61 However, for Ni-and Cu-based systems, the validation of these classic mechanisms faces significant challenges since the existence of high-valent species is under debate. [62][63][64] Instead, reaction mechanisms involving noninnocent ligands are widely proposed in this regard. 65,66 For instance, the carbonate and phenolate ligands in Ni-based mononuclear WOCs 13 and 14 were believed to be redoxactive centers in addition to the metal sites.…”
Section: Recent Progress In Designing Molecular Wocsmentioning
confidence: 99%
“…61 However, for Ni-and Cu-based systems, the validation of these classic mechanisms faces significant challenges since the existence of high-valent species is under debate. [62][63][64] Instead, reaction mechanisms involving noninnocent ligands are widely proposed in this regard. 65,66 For instance, the carbonate and phenolate ligands in Ni-based mononuclear WOCs 13 and 14 were believed to be redoxactive centers in addition to the metal sites.…”
Section: Recent Progress In Designing Molecular Wocsmentioning
confidence: 99%
“…The oxidation of Cu II (HOOH) accompanied by the loss of a proton finally leads to oxygen release and the regeneration of 12. (Figure 9, 13) has been recently reported to act as catalyst at high pH [52]. The metal center is bound by four nitrogen atoms from the ligand and a water molecule, featuring distorted trigonal bipyramidal geometry.…”
Section: 2 -Bipyridine and Related Ligandsmentioning
confidence: 99%
“…The CV of 13 displayed no current peaks below 1.0 V. On the other hand, an irreversible oxidation wave appeared at 1.27 V versus NHE with nearly four times as high current density as that of the complex-free solution. The (Figure 9, 13) has been recently reported to act as catalyst at high pH [52]. The metal center is bound by four nitrogen atoms from the ligand and a water molecule, featuring distorted trigonal bipyramidal geometry.…”
Section: 2 -Bipyridine and Related Ligandsmentioning
confidence: 99%
“…[3] In recent years, the development of first-row-metal-based WOCs, [3,4] such as manganese, [5] iron, [6] cobalt, [7,8] nickel, [9] and copper complexes, has attracted more attention. [10][11][12][13][14][15][16][17][18] Some of these earth-abundant molecular WOCs have displayed very high catalytic activities;for example, an observed rate constant (k obs )o f1 400 s À1 was obtainedf or a molecular cobalt porphyrin WOC in ap hosphate buffer solution (PBS) at pH 7. [8] Molecular copper catalysts have drawn particular attention for OER, owing to the diverser edox properties and well-studied coordinationc hemistry of copper complexes, as wella st he low cost and the high abundance of copper on earth.S ince the first molecular copper WOC was reported by Mayer and co-workersi n2 012, [10] an umber of single-site and multisite copper WOCs have been successively reported.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Molecular copper catalysts have drawn particular attention for OER, owing to the diverser edox properties and well-studied coordinationc hemistry of copper complexes, as wella st he low cost and the high abundance of copper on earth.S ince the first molecular copper WOC was reported by Mayer and co-workersi n2 012, [10] an umber of single-site and multisite copper WOCs have been successively reported. [11][12][13][14][15][16][17][18] Some studies have demonstrated that the catalytic activity and the Twoc opper complexes,[ ( L1)Cu(OH 2 )](BF 4 ) 2 [1; L1 = N,N'-dimethyl-N,N'-bis(pyridin-2-ylmethyl)-1, 2-diaminoethane] and [(L2)Cu(OH 2 )](BF 4 ) 2 [2, L2 = 2,7-bis(2-pyridyl)-3,6-diaza-2,6-octadiene],w ere prepared as molecular water oxidation catalysts. Complex 1 displayed an overpotential (h)o f1 .07 Va t 1mAcm À2 and an observedr ate constant( k obs )o f1 3.5 s À1 at h 1.0 Vi np H9.0 phosphate buffer solution,w hereas 2 exhibited as ignificantly smaller h (0.70 V) to reach 1mAcm À2 and a higher k obs (50.4 s À1 )t han 1 under identical test conditions.…”
Section: Introductionmentioning
confidence: 99%